Enabling low-voltage, peer-to-peer, quasi-real-time electricity markets through consortium blockchains. (15th April 2021) - Bischi, Aldo; Basile, Mariano; Poli, Davide; Vallati, Carlo; Miliani, Francesco; Caposciutti, Gianluca; Marracci, Mirko; Dini, Gianluca; Desideri, Umberto
Highlights: Design of peer-to-peer, quasi-real-time blockchain-based electricity market. Economic feasibility of Ethereum-based blockchain platforms, e.g. Energy Web Chain. Ad-hoc Ethereum-based, consortium blockchain, complying with real world standards. Sustainability, fairness for all players, privacy and transparency, cybersecurity. A proof-of-concept implementation comprehensive of the smart meter and loads. Abstract: Variable renewable energy sources are continuously increasing their share in the world energy mix. However, their uncertainty has a deep impact in the electric grid safe operation. One of the most promising solutions to tackle such challenge at a distribution grid level consists of quasi-real-time, peer-to-peer electricity markets. These can use the blockchain to be successfully implemented in a secure and privacy preserving way, making effective use of the increasing intelligence of Internet of Things appliances. Nevertheless, providing blockchain-based solutions compatible with the energy sector is not an easy task. In particular, in order to be compliant with typical electricity costs of the order of some €cents/kWh, blockchain transactions are required to be very cheap. Unfortunately, none of the existing research works took the issue of transaction costs into account. As a result, real-world feasibility of existing solutions is rather to be investigated. In this work, we propose an ad-hoc Ethereum-based consortium blockchain explicitly addressing this issue. Leveraging on this platform, we design a blockchain-based electricity market. The market consists of two-steps. The first (day-ahead) step settles the amounts and prices of the energy traded among peers. The second step is instead quasi-real-time, thus enabling the unexpected excess or lack of electricity to be directly negotiated on a peer-to-peer basis. Negotiations occurs without the need of any intermediary, except for the check of grid physical limits, performed by the distribution system operator. To demonstrate the functionality of the solution, a proof-of-concept has been implemented at the University of Pisa (Italy).